2018
DOI: 10.3168/jds.2017-14075
|View full text |Cite
|
Sign up to set email alerts
|

Extensive countrywide field investigation of subclinical mastitis in sheep in Greece

Abstract: The objectives of this work were (1) to investigate prevalence of subclinical mastitis, (2) to identify etiological agents involved, and (3) to study factors potentially predisposing ewes to subclinical mastitis. Milk samples were collected from 2,198 ewes in 111 farms with a total population of 35,925 ewes, in all 13 administrative regions of Greece, for bacteriological and cytological examination. Prevalence of subclinical mastitis was 0.260. Main etiological agents were staphylococci (Staphylococcus aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…In a recent study performed in Greece, that had evaluated the importance of various factors and their interactions by using multivariable analysis, it emerged that only the management system applied in farms (European Food Safety Authority, ) was of importance for mastitis (Vasileiou, Cripps, et al, ). The results indicated that mastitis occurred more frequently in farms managed under an intensive or semi‐intensive system (Vasileiou, Cripps, et al, ). “Management system” includes various aspects of flock husbandry and organization (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study performed in Greece, that had evaluated the importance of various factors and their interactions by using multivariable analysis, it emerged that only the management system applied in farms (European Food Safety Authority, ) was of importance for mastitis (Vasileiou, Cripps, et al, ). The results indicated that mastitis occurred more frequently in farms managed under an intensive or semi‐intensive system (Vasileiou, Cripps, et al, ). “Management system” includes various aspects of flock husbandry and organization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The potential effects of post‐milking teat dipping in ewes have not been studied as extensively as in cows (Bergonier et al, ; Vasileiou, Cripps, et al, ). Nevertheless, omission of the practice can lead to a 3‐fold increase in the prevalence of subclinical mastitis (Vasileiou, Cripps, et al, ).…”
Section: Non‐animal‐related Predisposing Factorsmentioning
confidence: 99%
See 3 more Smart Citations